MODEL LEMBAGA KEUANGAN MIKRO SYARI'AH PETANI GARAM DI PULAU MADURA - - Fathor A. S. (Trunojoyo University of Madura, 2010)
The aim of the study is to identify conditions and economic potential and local exchange systems, and check the model of micro finance institutions in accordance with local conditions syari'ah. The population in this study are all farmers of salt in 3 (three) District on the island of Madura is Sumenep districts, Pamekasan districts and Sampang districts are categorized lacquer with infinite number. Sample locations are determined by purposive sampling technique because not all villages that produce salt. The sample size of each village is determined every 10% of Head of the Family (KK). Analytical techniques used are preparticipatory rural appraisal techniques, economic auditing, social auditing (examinating local currency sistem), community and resources mapping and FGD (Focus Group Discussion). The analysis showed that the economic component that works at the local level more merchant dominant. In terms of socio-economic conditions of farmers increasingly tied to debt. Results from direct interviews with salt farmers, merchant and community leaders and village chiefs appears that the existence of institutions that could be an alternative 'institutions' which is currently expected to grow, including microfinance institutions syari'ah.